Ask Question
10 December, 03:12

What is the result of subtracting the second equation from the first x-3y=6 and - 8x-y=6

Answers (1)
  1. 10 December, 04:08
    Step-by-step explanation:

    Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation:

    x-3*y - (6) = 0

    Step by step solution:

    Step 1:

    Equation of a Straight Line

    1.1 Solve x-3y-6 = 0

    "y=mx+b" is the formula of a straight line drawn on Cartesian coordinate system in which "y" is the vertical axis and "x" the horizontal axis.

    In this formula:

    y tells us how far up the line goes

    x tells us how far along

    m is the Slope or Gradient i. e. how steep the line is

    b is the Y-intercept i. e. where the line crosses the Y axis

    The X and Y intercepts and the Slope are called the line properties. We shall now graph the line x-3y-6 = 0 and calculate its properties

    Graph of a Straight Line:

    Calculate the Y-Intercept:

    Notice that when x = 0 the value of y is 2/-1 so this line "cuts" the y axis at y=-2.00000

    y-intercept = 6/-3 = 2/-1 = - 2.00000

    Calculate the X-Intercept:

    When y = 0 the value of x is 6/1 Our line therefore "cuts" the x axis at x = 6.00000

    x-intercept = 6/1 = 6.00000

    Calculate the Slope:

    Slope is defined as the change in y divided by the change in x. We note that for x=0, the value of y is - 2.000 and for x=2.000, the value of y is - 1.333. So, for a change of 2.000 in x (The change in x is sometimes referred to as "RUN") we get a change of - 1.333 - (-2.000) = 0.667 in y. (The change in y is sometimes referred to as "RISE" and the Slope is m = RISE
Know the Answer?